Digital Tools Used in Face-to-face Higher Education: A Systematic Review - Polonia, Ana da Costa; Miotto, Angélica Inês; Suyo-Vega, Josefina Amanda (Revista Electrónica Educare, 2023)
Introduction. The higher face-to-face education can benefit from technological tools to promote, improve, and introduce new teaching methodologies. Method. This research aimed to characterize the digital resources/tools used to support the face-to-face modality and the challenges encountered in the introduction of these tools to this modality. The study implemented a systematic literature review; it examined the following databases: Scopus, Scielo, Proquest and Ebsco Host. Boolean operators “AND” and “OR” were used to compose the search equation (“Online teaching” OR “Online learning” OR “online education” OR “online tools “ OR “digitais tools” AND “university” OR “graduate” OR “undergraduate”) in Spanish, Portuguese, and English. The literature review was conducted between 2015 and 2021 in the areas of education and social sciences. Results. Out of the 14,801,280 articles found, only 11 were obtained through PRISMA systematization. It is necessary to explore the potential of digital tools in the face-to-face modality. This exploration is an essential competence to develop in higher education. Therefore, educational institutions should promote digital skills in both students and teachers. The use of digital tools can be categorized as content-oriented, collaborative, and for self-reflection. Conclusion. Students and teachers use technological resources in their lives, but there is still little investment on the part of teachers to integrate these resources in face-to-face classroom settings. This lack of investment has led to problems such as connectivity issues, technological incompetence of the actors, and difficulties in introducing digital tools in curricular and extracurricular activities.